Atitudes, habilidades, conhecimento e conscientização: o desenvolvimento de competências interculturais durante o intercâmbio - Aguiar, Italo Cavalcante (2016)
This study aimed to identify intercultural competencies developed by foreign students who participated in an exchange program at the Federal University of Ceará in the period between 2008 and 2015. Johnson et al (2006) conducted an extensive literature review on intercultural competence, from which noted that the literature dedicated to multicultural management devoted little attention to defining the concept of intercultural competence. For Fantini (2007), intercultural competence is defined as a group of skills needed to perform effectively and properly, the interaction with other people who are linguistically and culturally different from each other .The evaluation model of Intercultural Competence (AIC) by Fantini (2007) was used to identify and measure these intercultural skills. The research adopted a quantitative method of descriptive nature. It was applied in total 207 questionnaires with german, portuguese, spanish and french students who participated in an exchange program at the Federal University of Ceará between 2008 and 2015. For the treatment of the data, it was used descriptive statistics, the rotation method Varimax, the Cronbach alpha technique and the nonparametric test Kruskal-Wallis. The survey results showed that there was an increase in each of the components of the AIC Model (Knowledge, Attitudes, Skills and Awareness) by Fantini (2007), during the exchange students in the four surveyed nationalities. Portuguese students had a greater intercultural competence index at the beginning and end of the exchange, while the German students had the lowest intercultural competence index at the beginning of the exchange, and the Spanish students had a lower intercultural competence index at the end of exchange. However, it was the German students who had a higher growth in this intercultural competence index, from beginning to end of the exchange, followed by the French and Spanish students, respectively. On the other hand, the Portuguese students showed lower growth in intercultural competence index.